2016
DOI: 10.1021/acs.analchem.5b04605
|View full text |Cite
|
Sign up to set email alerts
|

Capillary Dielectric Barrier Discharge: Transition from Soft Ionization to Dissociative Plasma

Abstract: A capillary He dielectric barrier discharge was investigated with respect to its performance as a soft or dissociative ionization source. Spatiotemporal measurements of the plasma emission showed that in one voltage duty cycle the plasma evolved from a soft to dissociative ionization source. At the earliest time, the soft plasma was generated between the electrodes as well as outside the capillary forming the plasma jet. It was characterized by significant radiation arising only from He and N2(+), which are kn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 23 publications
0
39
0
Order By: Relevance
“…[17][18][19] The coincident plasma on the other hand can be attributed to a dissociative character unwanted in most soft ionization processes. 16 While it was already shown that the intensity of this plasma strongly depends on the charge coupled to the DBD and could be enhanced significantly by increasing the total electrode width of the used DBD, the mode change from an early soft plasma to a dissociative coincident plasma can only be understood with the ionization of the trace impurities. As can be seen from Fig.…”
Section: Measurements and Resultsmentioning
confidence: 99%
“…[17][18][19] The coincident plasma on the other hand can be attributed to a dissociative character unwanted in most soft ionization processes. 16 While it was already shown that the intensity of this plasma strongly depends on the charge coupled to the DBD and could be enhanced significantly by increasing the total electrode width of the used DBD, the mode change from an early soft plasma to a dissociative coincident plasma can only be understood with the ionization of the trace impurities. As can be seen from Fig.…”
Section: Measurements and Resultsmentioning
confidence: 99%
“…From [19], it was also observed that there is a minimum threshold for the helium mole fraction in the helium jet for the successful propagation of the plasma bullet. Recently many important experimental studies have been carried out providing very good insight into the characterization and understanding of these devices, the electric fields [20][21][22][23][24][25] and the different produced species [26][27][28][29][30][31]. However, in order to increase the understanding behind the operation of APPJ and to overcome some of the practical experimental limitations, numerical modelling has been increasingly used to simulate APPJ devices.…”
Section: Introductionmentioning
confidence: 99%
“…While for low frequencies one could expect ion losses to ions reaching the capillary walls during the long periods to be the culprit, this cannot be the case for higher frequencies. However, it was recently shown that the plasma inside a dielectric barrier discharge possess time-dependent properties [29,30], which could be an explanation for a frequency-dependent ionization behavior.…”
Section: Initial Parametric Study Of the Dielectric Barrier Dischargementioning
confidence: 99%